The Effects of Hypoxia in Patients with Atrial Septal Defect (ASD) and Eisenmenger Syndrome: A Case Report - Dyah Rachmasari; Elok Nurlisa Artiko; Abd. Rahim (Riviera Publishing, 2026)
Background: Atrial septal defect (ASD) is a congenital heart disease characterized by an opening in the interatrial septum, allowing abnormal blood flow between the atria. In untreated cases, long-standing left-to-right shunting may progress to pulmonary arterial hypertension and eventually Eisenmenger syndrome, a severe condition associated with chronic hypoxemia, cyanosis, secondary erythrocytosis, and multiorgan complications. Case Presentation: A 46-year-old female patient was referred to Kudungga Regional Hospital with intermittent shortness of breath that worsened over four days, bluish discoloration of the fingers and toes, chest pain, palpitations, tremors, edema, and productive cough. Physical examination revealed cyanosis, clubbing fingers, periorbital edema, oxygen saturation of 74%, cardiomegaly, systolic murmur, and pulmonary rales. Supporting examinations showed biatrial enlargement and right ventricular dilation on electrocardiography, cardiomegaly and pulmonary hypertension on chest X-ray, elevated hemoglobin and hematocrit levels, thrombocytopenia, and severe pulmonary arterial hypertension on echocardiography. Echocardiography also revealed a secundum ASD with bidirectional shunt, right atrial and ventricular dilatation, right ventricular hypertrophy, severe tricuspid regurgitation, and preserved ejection fraction. The patient was diagnosed with secundum ASD bidirectional shunt, severe pulmonary arterial hypertension, Eisenmenger syndrome, bronchopneumonia, and hypoxia-induced tremor. Management included oxygen therapy, fluid restriction, diuretics, antibiotics, mucolytics, sildenafil, digoxin, antiplatelet therapy, and symptomatic treatment. After eight days of hospitalization, the patient showed clinical improvement and was discharged for outpatient follow-up. Conclusion: This case highlights the significant impact of hypoxia in ASD patients with Eisenmenger syndrome, particularly in causing cyanosis, secondary erythrocytosis, hyperviscosity symptoms, and neurological manifestations such as tremor.